Increasing Motivation Awareness of Rights and Obligations of Students of SMK Negeri 3 Samarinda Through Civics Learning - Katmini, Katmini (Educationist: Journal of Educational and Cultural Studies, 2022)
This study aims to find out the causal factors of why students violate rights and deny obligations and whether Civics learning can increase the motivation for awareness of the rights and obligations of students at SMK Negeri 3 Samarinda. The results of this study indicate that from cases of violation of rights and denial of obligations committed by these students, it can be concluded that the factors causing the violation of rights and denial of obligations committed by students were caused by internal and external factors. Internal factors are the attitude and behaviour of egoism, lack of awareness of the nation and state, and not respecting and appreciating the rights of others. At the same time, the external factors are misuse of technology and the mild sanctions or fines given. PPKn subjects with KD Being responsive and proactive towards violations of rights and denial of citizens' obligations in society, nation and state with material cases of rights violations and denial of citizen obligations can increase awareness of their rights and obligations.